2022
DOI: 10.3390/horticulturae8070616
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Performance of Plum (Prunus domestica L.) Pollen from the Anthers Stored at Distinct Temperatures for Different Periods

Abstract: A study was conducted to investigate the effect of different storage periods and temperatures on pollen viability in vitro and in vivo in plum genotypes ‘Valerija’, ‘Čačanska Lepotica’ and ‘Valjevka’. In vitro pollen viability was tested at day 0 (fresh dry pollen) and after 3, 6, 9 and 12 months of storage at four different temperatures (4, −20, −80 and −196 °C), and in vivo after 12 months of storage at distinct temperatures. In vitro germination and fluorescein diacetate (FDA) staining methods were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The three water contents of pollens set in this study played a certain role in the pollen preservation, but when the temperature was reduced to −20 • C or below, pollen viability was no longer largely determined by the pollen water content. It may be caused by an insufficient gap between water content gradients [71,75]. A suitable method for short-term pollen preservation of G. sinensis was identified in this study.…”
Section: Pollen Preservation Of G Sinensismentioning
confidence: 92%
See 1 more Smart Citation
“…The three water contents of pollens set in this study played a certain role in the pollen preservation, but when the temperature was reduced to −20 • C or below, pollen viability was no longer largely determined by the pollen water content. It may be caused by an insufficient gap between water content gradients [71,75]. A suitable method for short-term pollen preservation of G. sinensis was identified in this study.…”
Section: Pollen Preservation Of G Sinensismentioning
confidence: 92%
“…It was found that the pollen germination rate was easily affected by storage temperature, storage time and pollen water content during pollen storage of G. sinensis in this study. A common feature of all pollen preservation treatments was a decrease in germination rate with increasing storage time, such as plum [75], pecan [49], rose [15], litchi [76] and chrysanthemum [77]. It was almost impossible for pollen stored at RT to germinate after 30 days, but it was still possible to maintain pollen vitality at low temperatures.…”
Section: Pollen Preservation Of G Sinensismentioning
confidence: 99%
“…However, there has been no published report about how many days caprifig fruits can be stored at 4 • C or while using an alternative storage temperature without losing pollen viability and germination. Several studies have shown that storing pollen at low temperatures is effective for their long-term preservation, including almond [17], cherimoya [18], mango [19], cherry [20], apple [21], pecan [22], gấc melon [23], plum [24], and rose [25]. However, because the fig's pollen ripens in the male fig fruits (caprifig), no studies have been found to determine the effect of pollen storage within caprifigs on the viability and germination of the pollen.…”
Section: Introductionmentioning
confidence: 99%
“…In such programs, the need to store pollen without losing germinability and fertility arises when it comes to larger hybridizations, in the case of nonsynchronous flowering and/or geographical isolation of parental species, or when dealing with the low vitality of currently available fresh pollen. So far, there are several reports in different fruit species showing that pollen stored at low temperatures is effective for short-or long-term preservation period (Martínez-Gómez et al, 2002;Alburquerque et al, 2007;Beltrán et al, 2019;^ali} et al, 2021;\or|evi} et al, 2022). About 70% of flowering plants disperse pollen at the binucleate stage, consisting of a vegetative nucleus and a generative nucleus ‡ the latter being the precursor of the two sperm cells (Brewbaker, 1967).…”
Section: Introductionmentioning
confidence: 99%